Prospective pilot intervention study to prevent medication errors in drugs administered to children by mouth or gastric tube: a programme for nurses, physicians and parents - Bertsche, Thilo; Bertsche, Astrid; Krieg, E.-M.; Kunz, N.; Bergmann, K.; Hanke, G.; Hoppe-Tichy, Torsten; Ebinger, Friedrich; Haefeli, Walter E. (Quality and safety in health care, 2010)
Background Drug administration in children is an error-prone task for nurses and parents because individual dose adjustment is often necessary, and suitable formulations for children are frequently lacking. Hence, in the absence of measures for their prevention, medication errors are likely to occur. - Objective To assess the error prevalence in drug administration by mouth or gastric tube before and after implementing a programme for quality improvement for nurses and parents. - Design, setting and participants Prospective, two-period cohort intervention study on a paediatric neurology ward of a university hospital where drug administration procedures of nurses and parents were consecutively monitored during the routine drug administration hours. - Main outcomes measure Prevalence of administration errors before and after implementing instructions for appropriate drug administration, and a teaching and training programme supported by information pamphlets. - Results Altogether, 1164 predefined administration tasks were assessed, 675 before and 489 after the intervention. Of these, 95.7% (after the intervention: 92.6%) were performed by nurses. Errors addressed by the intervention were reduced from 261/646 tasks (40.4%) to 36/453 (7.9%, p<0.001) in nurses and from 28/29 (96.6%) to 2/36 (5.6%, p<0.001) in parents. Errors in predefined categories concerning tablet dissolution, tablet storage, oral liquids, tablet splitting, administration by gastric tube and others were all considerably less frequent after the intervention (each p<0.001). - Conclusion Errors of drug administration by mouth and gastric tube represent a considerable and often neglected drug-related problem in paediatric inpatients. Targeted quality-improvement programmes can substantially and rapidly reduce error prevalence. Appropriate teaching and training of both nurses and parents supported by pamphlets was a highly efficient way to reduce error prevalence.
Gesehen am 25.01.2023